Membudayakan Praktik Jual-Beli Sejak Dini dalam Upaya Membentuk Jiwa Kewirausahaan Santri di Dayah Tradisional Aceh - Karuni Humairah Arta; Adelfa Yuriansa (Pencerah, 2023)
This article discusses the importance of introducing students to buying and selling practices in traditional Acehnese dayah at an early age in order to foster their entrepreneurial spirit. The significance of developing the entrepreneurial spirit of students in traditional Acehnese Islamic boarding schools as a means of enhancing future economic security. The research methodology then employs a descriptive-qualitative approach and the technique of purposive sampling. The findings indicate that entrepreneurship in dayah contributes significantly to the spiritual, academic, and social development of students. Buying and selling is an integral part of the curriculum and daily routine at the Islamic boarding school, allowing students to develop entrepreneurial skills and a competitive mindset. In addition, the practice of buying and selling helps students comprehend ethical principles and business responsibilities. This practice also strengthens the dayah's role as a center for entrepreneurship education, where students can develop business ideas, share knowledge, and work together to overcome obstacles. In conclusion, the practice of buying and selling at an Early childhood child in traditional Acehnese dayah has the potential to increase the entrepreneurial spirit of santri and encourage their participation in community development and regional economic growth. Implementing this practice in traditional Acehnese dayah is an important step in preparing students to face future challenges in the business world with greater preparedness.